Consistent Relationships Among Productivity Rate Methods in the NE Subarctic Pacific. Issue 2 (18th February 2021) - Timmerman, Amanda H. V.; Hamme, Roberta C.
Abstract: Phytoplankton photosynthesize in surface waters, exporting organic carbon to depth through the biological pump. Quantifying productivity and the export of carbon is important to understanding the global carbon cycle and predicting its future changes. An issue in quantifying rates is that the many existing methods are not all equivalent, making comparisons between studies using different methods challenging. Our goal is to compare in situ and in vitro methods in order to identify where methods agree in the NE subarctic Pacific. During this study, we measured productivity using two in situ methods (oxygen/argon ratio and triple oxygen isotope mass balance approaches) and four in vitro methods ( 13 C, NO 3 − 15, NH 4 + 15, and H2 18 O uptake rates through incubations), and compared the results with one satellite‐based productivity estimate. The in situ carbon export method was consistently higher than the in vitro method, likely due to dissolved organic matter release not included in our incubation measurements. Upwelling bringing low‐O2 water to the surface and the interaction between bloom dynamics and a method's inherent time of integration cause outliers from the relationship. In contrast, in situ and in vitro methods for estimating gross primary production were consistent across a wide range in rates. We find that chlorophyll‐a concentration is strongly related to many of our measured rates. Satellite estimates of primary production are consistently different from 13 C incubations. Our identification of consistent trends and causes for disagreement will allow observations from one method to be converted to another, facilitating future comparisons across studies. Plain Language Summary: Phytoplankton in the surface ocean photosynthesize, taking up carbon dioxide and producing oxygen. Phytoplankton form the base of the food web and play an important role in transferring carbon to the deep ocean, away from the atmosphere. Quantifying how fast phytoplankton grow and how much carbon makes it out of the surface waters will help predict future climate. One issue preventing accurate quantification is that different methods disagree, making it difficult to compare between studies. We find there are consistent differences between marine productivity methods in the NE Pacific. Incubations that remove water from the environment tend to have lower estimates for carbon transferred out of surface waters than methods that measure the natural abundance of gases. At higher rates, methods are less consistent. In contrast, both method types estimating gross photosynthesis rates are consistent over a wide range of rates. We are able to establish consistent relationships between an incubation method and other methods, including satellite estimates and chlorophyll concentrations. The consistent agreement between rate measurements expands comparisons that can be made between studies that use different methods, allowing for a better understanding of phytoplankton's role in controlling carbon processes. Key Points: We identify consistent relationships among six productivity rate methods as well as with chlorophyll‐a in the NE subarctic Pacific region Dissolved organic matter release likely causes incubation‐based carbon export to be consistently low compared to the in situ estimate Upwelling events and the timing of bloom dynamics influence outliers from the consistent relationships